MIS problems in a batch processing environment - P. J.S. Bruwer; C. E. Pretorius; H. S. Steyn (South African Journal of Business Management, 1983)
Performance measures like profits are an important criterion for evaluating the success of computer-based management information systems. However, the study of performance of a computer-based information system is difficult because of measurement problems and a large number of variables which affect performance. Many technically well-designed systems have failed to achieve their objectives or to work at all, because important factors which can contribute substantially to the success of an MIS were ignored. Based on a research project carried out in a large organization where the computer-based systems operate on a batch data processing system, this paper discusses some of the major problems which can lead to the total failure of an MIS.
Keywords: 650